Cognitive Representation of Human Action: Theory, Applications, and Perspectives - Seegelke, Christian; Schack, Thomas (Frontiers in Public Health, 2016)
In this perspective article, we propose a cognitive architecture model of human action that stresses the importance of cognitive representations stored in long-term memory (LTM) as reference structures underlying and guiding voluntary motor performance. We introduce an experimental approach to ascertain cognitive representation structures, and provide evidence from a variety of different studies, ranging from basic research in manual action to application-oriented research such as athlete performance and rehabilitation. As results from these studies strongly support the presence of functional links between cognitive and motor processes, we regard this approach as a suitable and valuable tool for a variety of different disciplines related to cognition and movement. We conclude this article by highlighting current advances in ongoing research projects aimed at improving interaction capabilities in technical systems, particularly for rehabilitation and everyday support of the elderly, and outline future research directions.